RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PROYEK PADA CV.GRAHA RAYA CONSULTANT - Fauzan Amri, Muhammad; Aditya Harahap, Calvin (Universitas Majalengka, 2024)
Project Management Information System is needed to support the effectiveness of project management at CV. Graha Raya Consultant. Currently, the company faces challenges in managing scattered project information and inefficient coordination processes. This study aims to design and implement a web-based project management information system that can assist in monitoring, managing data, and reporting projects. The methodology used is the waterfall-based software development method. This system is expected to help improve efficiency in project management and minimize errors caused by manual recording. The test results show that the information system developed is able to meet the company's needs and facilitate management in supervising each stage of the project.